Factors influencing the urge to buy impulsively of Vietnamese online buying customers towards Biti’s Hunter sport shoes - Nguyen, Xuan-Nhi; Hoang, Hung Cuong; Vu, Trung-Nghia (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Our study investigates the factors that drive Vietnamese online shoppers in Ho Chi Minh City (HCMC) to make impulsive purchases of Biti’s Hunter sports shoes (BHS), using the Stimulus-Organism-Response (S-O-R) theory and the Technology Acceptance Model (TAM). Mixed methods are applied: in-depth interviews with ten regular online shoppers and focus group discussions with e-commerce managers for qualitative data collection, and survey techniques to gather quantitative data from 319 online shoppers. Data analysis was performed using SPSS 22.0 and AMOS 22.0. Our findings reveal five factors as a stimulus - visual appeal, website ease of use, product availability, portability, and social influence – and three factors as an organism - instant gratification, impulsiveness, and trust, that lead to the response of urge to buy impulsively. Significant positive effects are found among these constructs, except the relationship between portability and impulsiveness, visual appeal, social influence, trust, instant gratification, and urge to buy impulsively.